(untitled) (The Review of Diabetic Studies, 2024)
Background: World health organization conceptualized Referrals are a dynamic process whereby a healthcare provider at one level of the system, lacking the authority or resources to appropriately manage a patient’s clinical condition, looks to another facility at the same or higher level to assist in the treatment route. One of the mainstays of the primary care system is referrals. Study objectives: To assess the knowledge and attitudes towards AIDS among practicing physicians in the family medicine clinics , Saudi Arabia. Methods; Research design : cross sectional , descriptive research design was utilized to conduct this study; Settings :It was conducted at 10 family medicine clinics ( The Western Region is home to ten (10) family medicine clinics, including the National Guard Training Center, Baharah clinics, Madinah clinics, Sharaie clinics, Um Alsalam clinics, Jazan clinics, Yanbu clinics, King Faisal residential city clinics (KFRCC)-Jeddah, and King Khalid residential city clinics (KKRCC)-Taif clinics.) , at Jeddah at Saudia Arabia ; participants: 276 family medicine physician was included in this study. Questions about knowledge and practice of referral systems were included in the questionnaire. Using a scoring system that adds up 1 for right answers and 0 for wrong replies, the questionnaire’s examined variables are scored. Findings: The majority of doctors (65.2% & 94.2%, respectively) knew and used the referral system well. Physicians employed by accredited versus non-accredited facilities had substantially more good knowledge (81.8% vs. 50%). Additionally, doctors who worked in family health units had a much greater percentage of good practices than those who worked in family health centers (96.8% vs. 66.7%). Based on the majority of the factors examined, there is little difference between knowledge and practice. To enhance the referral system, doctors recommended developing referral criteria, reforming medical education, changing payment methods, and creating culture-building activities (97.8%, 94.2%, 97.8%, and 97.8%, respectively). Conclusion: The paper recommends more orientation programs for both groups of physicians and urges the private sector physicians to be more involved in Ministry of Health training programs and activities. Cooperation in referral between the private sector and government hospitals is seen as one way of improving health care in Saudi Arabia.